Dinamika dan manfaat menghafal al-qur’an dalam kehidupan mahasiswa - Putri, Naura Deviyanti Nivia (Maliki Interdisciplinary Journal, 2025)
The phenomenon of university students who simultaneusly live as mahasantri presents a unique dynamic in both academic and spiritual life. One of the greatest challenges they must face is maintaining consistency in memorizing the Qur’an amid a demanding academic schedule. This article aims to describe the various challenges experienced by mahasantri who memorize the Qur’an while also highlighting the benefits and blessings gained throughout the process. The writing method employed is a literature review combined with reflections on the empirical experiences of mahasantri. The findings indicate that the main challenges lie in time management, academic workload, and social pressure. On the other hand, Qur’an memorization provides inner peace, discipline, and spiritual motivation that strengthens academic pursuits. With effective time management strategies, a supportive environment, and sincere intention, these challenges can be transformed into a means of personal growth. This article emphasizes that memorizing the Qur’an while pursuing higher education is not only possible but also adds significant value to the character formation of Muslim students.